Factors influencing job stress among Malaysian Traffic Police Officers / Muhamad Khalil Omar ...[et al.] - Omar, Muhamad Khalil; Aluwi, Ainie Hairianie; Hussein, Norashikin; Mohd, Idaya Husna; Rusdi, Syezreen Dalina (UiTM Cawangan Johor, 2019)
Traffic police officers face many challenges in their line of duty to the protect the country and its citizens. Despite, the significance of traffic police officers to the community and the country, lack of studies specifically on how workload, reward system, and work-life balance affects job stress among traffic police officers are apparent. Job stress creates tension in the working environment, and this research aims to solve and find out what is the cause for job stress. The observational review was finished by utilizing a poll and questionnaires as a measuring instrument. The questionnaires were composed based on the literature review and have inquiries and things significant to the underlying research issues by using five-point Likert scale type questions. Survey data were gathered from questionnaires distributed to 300 respondents at a Traffic Police Office in Kuala Lumpur, Malaysia. A total of 100 returned questionnaires were used in statistical analysis. The results indicated that the relationship between work-life balance and job stress was significant while there were no significant relationships between workload, reward system, and job stress. The limitations of this study are addressed and suggestions for practitioners and future research were recommended.